A MORPHOLOGICAL STUDY OF CELIAC, SUPERIOR MESENTERIC AND INFERIOR MESENTERIC ARTERIES IN ATHEROSCLEROSIS - Naeem, Amjad; Nasim, Nadia; Ihsan, Umaira; Masood, Atika (Journal of Ayub Medical College Abbottabad, 2012)
Background: Depolymerisation of acid-mucopolysaccharides results in the loss of metachormasia of the ground substance followed by visible fibre crumbling, complete dissolution and replacement by lipid droplets and cholesterol. The objective of this study was to assess the distribution of different atherosclerotic lesions in celiac, superior mesenteric and inferior mesenteric arteries relation to age and sex. Methods: A prospective descriptive observation study was conducted at Mortuary of King Edward Medical University Lahore, and Department of Pathology Allama Iqbal Medical College Lahore. A total of 30 human autopsies were carried out. Celiac, Superior mesenteric and inferior mesenteric arteries were taken out and opened length-wise. One to four areas of tissue were taken from each artery for histological examination. Slides were prepared from each paraffin block. Sections were stained with haematoxylin and eosin. Special stains were performed on sections to display each component of atherosclerosis. Results: The fibrolipid plaques were seen in 6 cases. The complicated lesions were present in 5 cases. Of these, 4 showed ulceration and 1 showed thrombus formation. The calcified lesions were observed in 5 cases. The morphological changes in media and elastica were present in 4 cases. In superior mesenteric artery fatty streaks were present in 8 cases. The fibrolipid plaques were confirmed in 5 cases. Three cases showed ulceration, 1 case showed intimal vascularisation, haemorrhage, and thrombus formation. The calcified lesions were present in 2 cases. The morphological changes in media and elastica were seen in 4 cases in anterior mesenteric artery. Fatty streaks were present in 8 cases. The fibrolipid plaques were grossly observed in 6 cases. The complicated lesions were present in 4 cases; of these, 3 cases showed ulceration, and 1 showed intimal vascularisation and haemorrhage along with thrombus formation. The calcified lesions were present in 3 cases. The morphological changes in media and elastica were present in 4 cases. Conclusion: This data indicates the incidence of ischemic changes in abdominal viscera due to atherosclerotic narrowing. Keywords: Celiac, Superior, Inferior, mesenteric, atherosclerosis, arteries